Disclosure Level before and after the application of an IPSAS based accounting system: The case of Greece - Vrentzou, Eleni (International Conference on Business and Economics - Hellenic Open University, 2023)
Purpose – The purpose of this paper is to compare the level of central government financial information disclosed in the annual financial statements before and after the adoption of an accounting system based on International Public Sector Accounting Standards (IPSAS). A comparison of this disclosure level to the IPSAS required disclosure level is also performed. Design/methodology/approach – This study uses a checklist of disclosure items used to measure the IPSAS disclosure level and compare this with the score of the government financial statements in Greece for the years 2011-2020. Findings – The results show significant differences between the disclosure level of the government financial statements before and after the application of an IPSAS based accounting system. Specified application difficulties explain the difference between the required IPSAS disclosure level and the level already achieved by the Greek public accounting system. Practical implications – The research findings are potentially relevant to academics and practitioners since it provides evidence on the improvement of the disclosure level on the process of IPSAS application. It also identifies difficulties faced on this process and explains how they affect the disclosure level achieved. JEL CODE: H83 Key words: International Public Sector Accounting Standards, Disclosure, Public Sector Accounting